2010
DOI: 10.1159/000319445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paricalcitol and Enalapril on Atherosclerotic Injury in Mouse Aortas

Abstract: Aims: This study investigated the protective effect of vitamin D analog paricalcitol combined with angiotensin-converting enzyme inhibitor (enalapril) on aortic oxidative injury in atherosclerotic mice. Methods: Female mice were treated for 16 weeks as follows: (1) ApoE deficient + vehicle, (2) ApoE deficient + paricalcitol (200 ng 3 times a week), (3) ApoE deficient + enalapril (30 mg/l in drinking water), (4) ApoE deficient + paricalcitol + enalapril, and (5) wild-type controls. Results: ApoE-deficient mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 95 publications
4
43
1
Order By: Relevance
“…Treatment with enalapril also prevented the increase as did cotherapy with the two drugs. Recent studies from members of our group also showed amelioration by paricalcitol and enalapril of uremiainduced NADPH oxidase activity in rat cardiac tissue (20) and of apolipoprotein E knockout-induced NADPH oxidase activity in the mouse aorta (21). Since active vitamin D compounds have been shown to negatively regulate the RAAS (26,56), the inhibition of p22 phox by either enalapril or paricalcitol points to a role for the RAAS in the oxidative stress seen in the kidney in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…Treatment with enalapril also prevented the increase as did cotherapy with the two drugs. Recent studies from members of our group also showed amelioration by paricalcitol and enalapril of uremiainduced NADPH oxidase activity in rat cardiac tissue (20) and of apolipoprotein E knockout-induced NADPH oxidase activity in the mouse aorta (21). Since active vitamin D compounds have been shown to negatively regulate the RAAS (26,56), the inhibition of p22 phox by either enalapril or paricalcitol points to a role for the RAAS in the oxidative stress seen in the kidney in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…We speculate that paricalcitol decreases contrast-induced explosion of serum MDA and renal TBARS levels, therefore ameliorating the renal histopathological findings (tubular necrosis, proteinaceous casts and medullary congestion) in the paricalcitol plus CIN group. Of note, paricalcitol has been shown to improve cardiac oxidative injury in uremic and aortic oxidative injury in atherosclerotic rats [9,23]. Paricalcitol has been shown to attenuate ciclosporin Ainduced nephropathy by suppression of inflammatory and apoptotic factors through inhibition of some protein kinase-signalling pathways [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been recently reported that the combination of paricalcitol and enalapril treatment ameliorates oxidative injury by suppressing reactive oxygen species generating enzyme NADPH oxidase activity and by up regulating the antioxidant defense system in a uremic rat model of atherosclerosis. 11 It is not known, however, whether paricalcitol can protect against oxidative stress in amikacin-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%